DESAIN IMPLEMENTASI ROUTING JARINGAN KOMPUTER DENGAN MENGGUNAKAN CISCO - Husni, Mochamad (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2012)
Advancement of computer network technology is developing very fast, especially the technology of the Internet. Besides the hardware technology is constantly evolving, technology application software is also progressing very rapidly. One form of Internet network technology advances that are being developed and popular as this is a used Cisco Router on a computer network. Keywords: Design and Implementation, Dynamic Routing, Computer Networking, Cisco Router.